Skipping stones - Le Roux, Jade-Eden (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
My thesis takes the form of a novella exploring suicide and the unanswered questions it leaves. The main protagonist is a young girl who struggles to come to terms with her best friend's suicide. The work is situated in contemporary South Africa, where inequality and depression is rife, especially among young people, and social media too often provides a smokescreen to conceal emotions. My writing is motivated by my desire to explore the human condition and the world around me, through my own subjective lens of experience. By working between fact and fiction I seek to trouble conventional narratives attached to suicide and highlight the subjectivity of truth. I am influenced by Lydia Davis's ability to write obliquely about loss, and her light-handed approach to emotionally charged topics; Susan Steinberg's dark motifs, vivid imagery, and her fragmented narrative that captures the characters' responses to trauma and interrogates the notion of truth; Lidia Yuknavitch's cinematic imagery and immediacy of tone and compact storytelling; and Kate Zambreno's poetic prose that lends itself to clear societal commentary.
Keywords: Creative writing (Higher education) -- South Africa; South African fiction (English) 21st century; Suicide in literature